2018
DOI: 10.1111/jvs.12611
|View full text |Cite
|
Sign up to set email alerts
|

Individual species–area relationships in temperate coniferous forests

Abstract: Questions What drives individual species–area relationships in temperate coniferous forests? Location Two 25.6‐ha forest plots on the Pacific Slope of North America, one in California, and one in Washington State. Methods We mapped all trees ≥1 cm in diameter and examined tree species diversity of their local neighbourhoods by calculating the individual species–area relationship for each species and for each of three diameter classes (saplings, mature trees and large‐diameter trees). Results In the California … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
1
23
1
Order By: Relevance
“…In this study, we analyzed the patterns of local species richness and their associations with functional trait syndromes in the Jianfengling FDP, the largest FDP worldwide. In contrast with other researches (Wiegand et al 2007, Yang et al 2013, Das et al 2018, we found that facilitation played an important role in maintaining local species richness patterns. In addition, another important contribution of the study was to determine the associations between local species richness and plant functional trait syndromes.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In this study, we analyzed the patterns of local species richness and their associations with functional trait syndromes in the Jianfengling FDP, the largest FDP worldwide. In contrast with other researches (Wiegand et al 2007, Yang et al 2013, Das et al 2018, we found that facilitation played an important role in maintaining local species richness patterns. In addition, another important contribution of the study was to determine the associations between local species richness and plant functional trait syndromes.…”
Section: Discussioncontrasting
confidence: 99%
“…, Das et al. ), we found that facilitation played an important role in maintaining local species richness patterns. In addition, another important contribution of the study was to determine the associations between local species richness and plant functional trait syndromes.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Fine-scale spatial pattern plays an important role in mediating post-fire effects, either through density-dependent mortality or aggregated post-fire forest development [20,21]. The importance of spatial heterogeneity to the correct calculation of landscape carbon [22][23][24] and remnant forest patches (e.g., refugia [25][26][27][28]) has been well established, but the spatial distribution of fire-caused mortality remains understudied.…”
mentioning
confidence: 99%